2007
DOI: 10.1002/dev.20203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methamphetamine exposure during prenatal and preweaning periods lasts for generations in rats

Abstract: Our previous studies demonstrated that methamphetamine (MA) administration during gestation and/or lactation affects maternal behavior in rats and that birth weight and sensory-motor coordination of their pups are also influenced. The present study tested the hypothesis that the effect of MA induces long-term changes affecting second generation of rats that were not exposed to the drug. Adult females exposed during prenatal and preweaning periods to 5 mg/kg MA daily, were examined for regularity of estrous cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
2
18
1
Order By: Relevance
“…In rodents, MA is toxic to dopaminergic and serotonergic neurons(42;43) and neurotoxic effects on serotogenetic neurons produce neurochemical alternations in the central nervous system(44;45). Prenatal MA exposure in 3 week old rats (equivalent to approximately age 5 years) demonstrate impaired postural motor movements(46) and these abnormal postural movements can still be noted in the second generation of rats exposed to MA prenatally(47). Administration of MA to laboratory animals also results in delayed motor development(48;49) and in pregnant mice, MA administration to the mother leads to dopaminergic nerve terminal degeneration and long term motor deficits in the exposed offspring(50).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, MA is toxic to dopaminergic and serotonergic neurons(42;43) and neurotoxic effects on serotogenetic neurons produce neurochemical alternations in the central nervous system(44;45). Prenatal MA exposure in 3 week old rats (equivalent to approximately age 5 years) demonstrate impaired postural motor movements(46) and these abnormal postural movements can still be noted in the second generation of rats exposed to MA prenatally(47). Administration of MA to laboratory animals also results in delayed motor development(48;49) and in pregnant mice, MA administration to the mother leads to dopaminergic nerve terminal degeneration and long term motor deficits in the exposed offspring(50).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this was due to maternal choice or to advice from care-givers is uncertain as milk amphetamine levels have been shown to be up to seven times higher than maternal plasma 31 32. We have previously demonstrated that breast milk feeds, even without the pacifying effect of suckling, ameliorates the severity of opiate withdrawal33 and further study regarding the interaction between amphetamines and lactation is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alterations in the levels and activity of the noradrenergic and serotonergic systems have been demonstrated in animals exposed to either amphetamine or methamphetamine 78-80. Some of the functional consequences (such as impaired sensory-motor coordination) of prenatal methamphetamine exposure are transmitted to the next generation of offspring 81. These findings demonstrate that prenatal amphetamine or methamphetamine exposure leads to a complex behavioral phenotype with similarly complex molecular and cellular roots.…”
Section: Effects Of Illegal Drugs Of Abusementioning
confidence: 92%